Molecular analysis of the APC and MUTYH genes in Galician and Catalonian FAP families: a different spectrum of mutations? - Gómez-Fernández Nuria; Castellví-Bel Sergi; Fernández-Rozadilla Ceres; Balaguer Francesc; Muñoz Jenifer; Madrigal Irene; Milà Montserrat; Graña Begoña; Vega Ana; Castells Antoni; Carracedo Ángel; Ruiz-Ponte Clara (BMC, 2009)
Abstract Background Familial adenomatous polyposis (FAP) is an autosomal dominant-inherited colorectal cancer syndrome, caused by germline mutations in the APC gene. Recently, biallelic mutations in MUTYH have also been identified in patients with multiple colorectal adenomas and in APC-negative patients with FAP. The aim of this work is therefore to determine the frequency of APC and MUTYH mutations among FAP families from two Spanish populations. Methods Eighty-two unrelated patients with classical or attenuated FAP were screened for APC germline mutations. MUTYH analysis was then conducted in those APC-negative families and in 9 additional patients from a previous study. Direct sequencing, SSCP analysis and TaqMan genotyping were used to identify point and frameshift mutations, meanwhile large rearrangements in the APC gene were screened by multiplex ligation-dependent probe amplification (MLPA). Results APC germline mutations were found in 39% of the patients and, despite the great number of genetic variants described so far in this gene, seven new mutations were identified. The two hotspots at codons 1061 and 1309 of the APC gene accounted for 9,4% of the APC-positive families, although they were underrepresented in Galician samples. The deletion at codon 1061 was not found in 19 APC-positive Galician patients but represented 23% of the Catalonian positive families (p = 0,058). The same trend was observed at codon 1309, even though statistical analysis showed no significance between populations. Twenty-four percent of the APC-negative patients carried biallelic MUTYH germline mutations, and showed an attenuated polyposis phenotype generally without extracolonic manifestations. New genetic variants were found, as well as the two hotspots already reported (p.Tyr165Cys and p.Gly382Asp). Conclusion The results we present indicate that in Galician patients the frequency of the hotspot at codon 1061 in APC differs significantly from the Catalonian and also other Caucasian populations. Similar results had already been obtained in a previous study and could be due to the genetic isolation of the Galician population. MUTYH analysis is also recommended for all APC-negative families, even if a recessive inheritance is not confirmed.